Working Effectiveness Of Batu Ix Subdistrict Office, Tanjungpinang East Sub-District, Tanjungpinang City : Efektifitas Kerja Kantor Kelurahan Batu Ix Kelurahan Tanjungpinang Timur Kota Tanjungpinang - Satriadi Satriadi; Charly Marlinda; Imran Ilyas; Laras Ayu Savitri (Academia Open, 2023)
This study investigates the work effectiveness of employees within a local governmental context. Focused on the Village Office of Batu IX, East Tanjungpinang District, Tanjungpinang City, the research employs a qualitative descriptive analysis method with data triangulation. The findings reveal existing deficiencies in work effectiveness, spanning service provision, public order implementation, and infrastructural support. However, the study also identifies the employees' capacity to adeptly address challenges through coordination and gradual problem-solving. These insights underscore the complexity of achieving work effectiveness within the public sector, hinting at potential pathways for improvement and adaptation. Highlights: Complex Public Sector Dynamics: Revealing challenges and deficiencies in work effectiveness within a local governmental context. Adaptive Problem-Solving: Employees demonstrate adeptness in addressing issues through coordination and staged resolutions. Potential for Improvement: Identifying prospects for enhancing work effectiveness through adaptative strategies and collaborative efforts. Keywords:Work Effectiveness, Public Sector, Employee Adaptation, Challenges, Coordination.